Onset Features and Subsequent Clinical Evolution of Childhood Diabetes over Several Years - Lipton, Rebecca B. (2011)
AIM: To explore whether it is possible to predict a child's eventual diabetes phenotype using characteristics at initial presentation, we reassessed 111 young patients on average 7.8± 4.2 (2.2–19.7) [mean±SD (range)] years after diagnosis. METHODS: Medical records at diagnosis for 111 patients, aged 0–17, were compared with their followup characteristics including stimulated C-peptide (CP), and islet autoantibodies (AB). RESULTS: Initially, 18 patients were obese; 9 displayed other type 2 diabetes (T2DM) features (polycystic ovary syndrome, acanthosis, diagnosed T2DM); the remaining 84 had a classic type 1 diabetes (T1DM) presentation. At follow-up, 83 patients (75%) with no measured CP were classified as T1DM; 17 (15%) were CP+ and AB- and thus considered T2DM. Eleven with both T1DM and T2DM features were classified as having mixed diabetes phenotype (MDM). One-fifth (22 subjects) changed presumed phenotype at follow-up. In multivariable models, T1DM patients were younger at diagnosis, had higher initial glucose values, were more likely to have experienced ketoacidosis, and less likely to be obese or of African-American ethnicity. CONCLUSIONS/INTERPRETATION: 10% of subjects had MDM and 15% had T2DM at ~8 years' duration. Although no onset feature was completely reliable, ketoacidosis and hyperglycemia were more likely to predict T1DM; obesity and African American ethnicity made T2DM more likely. At diagnosis, features of T2DM in addition to obesity were strongly predictive of eventual T2DM phenotype. Given the significant percentage who changed or had mixed phenotype, careful tracking of all young people with diabetes is essential to correctly determine eventual disease type.